A pedagogia na minha vida: relatos e reflexões de uma jornada de formação, educação e transformação social - Ferreira, Sebastiana da Silva (Brasil, 2024)
This academic memorial aims to report the academic trajectory of student Sebastiana da Silva Ferreira during her Pedagogy course at the Federal University of Amazonas – UFAM and discuss her challenges and difficulties encountered during the course. The document begins with an introduction that contextualizes the choice for the Pedagogy course, highlighting the personal and professional motivations that influenced this decision. Next, academic training is presented, detailing the stages of primary, secondary and higher education, with emphasis on the subjects studied, the projects developed and the main learning obtained. In the last chapter, professional experience in supervised internships in Early Childhood Education, Elementary Education and School Management is discussed. The contributions of these experiences to the construction of a pedagogical identity and the development of skills essential to the exercise of the teaching profession are discussed. Finally, the work presents a critical reflection on the academic trajectory, highlighting the main challenges and lessons learned, and points out future perspectives in the pedagogical career, with an emphasis on the importance of continued training and the commitment to quality education. This TCC contributes to the understanding of the multiple dimensions of Pedagogy training, offering a comprehensive and reflective view of the process of building pedagogical knowledge and professional performance in the educational field.